Scleredema Diabeticorum with Superimposed Cellulitis and Abscess Formation - Binav Shrestha; Eliza Sharma; Osama Mukhtar; Jaspreet Kaler; Shivani Thapa; Mazin Khalid (Case Reports in Endocrinology)
Scleredema diabeticorum is a rare cutaneous manifestation of diabetes mellitus. We present a case of an obese male with poorly controlled diabetes who came to the hospital with upper back pain and subsequently developed sepsis due to a small deep-seated abscess in his back that was drained and treated with antibiotics. He was also found to have extensive induration of the skin over his back and neck. Skin biopsy confirmed the diagnosis of scleredema diabeticorum.